(untitled) (Вестник КазНУ. Серия Экономическая, 2016)
The need for the formation of a new tax system came with the acquisition of independence of Kazakhstan and the country’s transition to a market economy. Market economy distinguishes competitiveness and self-regulation. Kazakhstan was the first CIS country has created progressive tax legislation. State adjusting tax policy provides country’s economic development. A modern tax system of Kazakhstan is aimed at the formation of the country’s central financial resources and as close as possible to international. The tax system of the state must continuously improve and learn from the experience of more developed countries. The main objective of the Strategic Development Tax Service is the creation of high- tax service to the community satisfaction. In modern conditions the intensification of entrepreneurial activity, increasing fiscal literacy, one of the problems with the tax service is the quality of tax administration. Modernization of tax service will have a positive impact on the administrative burden elimination double existed in the form of duplication of inspections, reporting forms, various levels of application of legislation and the provision of public services. As a result, in the country, a new system of interaction between the state and business, this is aimed at creating favorable conditions for business development. And this, in turn, will attract new investors to our country’s joining the 50 most developed countries of the world.